Music and dreams: a review - Olbrich, Kate Isobel; Schredl, Michael (International journal of dream research, 2019)
The purpose of this paper is to review scientific studies of music dreams and also touch the area of creative music dreams, i.e., dreams inspiring new music. Different types of music dream categories will be defined. In large sample, the percentage of music dreams in relation to all remembered dreams ranges from 4% to 8%. The literature indicates that musicians tend to experience more music dreams than non-musicians. The positive correlation between musical activities in waking life and music dream percentage supports the continuity hypothesis of dreaming. Also in line with the continuity hypothesis are the findings that music dreams are more positively toned than dreams in general. As research regarding this topic is still in its infancy, there are several interesting topics for the future studies, e.g., incubating creative music dreams, stimulating the sleeper with music, or the relationship between music and sleep-dependent memory consolidation.
Gesehen am 08.10.2019